Management of antithrombotic agents and current issues in patients undergoing endoscopic submucosal dissection - Chan Hyuk Park (Society of Gastrointestinal Intervention, 2019)
Postoperative bleeding is a common adverse event in endoscopic submucosal dissection (ESD) and may be life-threatening. Postoperative bleeding occurs frequently in patients treated with antithrombotic agents, including aspirin, antiplatelet agents, warfarin, and non-vitamin K-dependent oral anticoagulants. Due to the aging population and the increase in the risk of thromboembolic disease, the number of patients who require antithrombotic therapy has increased. To date, several clinical studies have been conducted and several global guidelines have been updated. Nevertheless, determining the optimal use of antithrombotic agents in patients undergoing ESD is still challenging, and recommendations for the use of these agents vary slightly across different guidelines. In this review, I summarized the current guidelines and discussed several ongoing issues with the management of antithrombotic agents in patients undergoing ESD.